Speech Acts in Post-Apocalyptic Games: The Last of Us (2014) - Colăcel Onoriu (Messages, Sages and Ages, 2017)
Among everything else post-apocalyptic video games have come to stand for, notions of in-group versus out-group communication are paramount. The Last of Us (2014, Naughty Dog/Sony Computer Entertainment) is a case in point. I look into the game’s use of subtitles and didactic texts in order to find out to the extent speech acts shape the player’s understanding of what the video game is. As an understudied aspect of video games, HUD or menu elements, as well as characters’ exchanges and voice-over narration, disclose what it is like to be alive, dead or in-between. Essentially, they show the tensions between the avatar and the gamer: the hero makes all of the decisions by himself and the player has to abide or stop playing all together. The avatar’s identity comes alive through speech acts, while the player is left outside decision-making processes. Survival horror gaming, with a religious twist, gives insight into the in-game discussion on the representation of the zombie rather than on the zombie experience as such. On screen, the interplay between speech acts and written language amounts to a procedural language, which suggests that variability in language creates an environment conducive to learning. Particularly, language use is all about group values and communication styles that should help gamers tell apart friends from enemies, good from evil and, finally, people from zombies.